Near‐surface ventilation as a key for modeling the thermal regime of coarse blocky rock glaciers. (1st August 2018) - Pruessner, Luisa; Phillips, Marcia; Farinotti, Daniel; Hoelzle, Martin; Lehning, Michael
Abstract: In a changing climate, ice‐rich permafrost features such as rock glaciers will experience drastic changes. Modeling the heat transport through the blocky surface layer with its large interstitial pore spaces poses some challenges as various modes of non‐conductive heat transport—advective forms in particular—can occur. Here, we show that the 1D physics‐based model SNOWPACK can be used with a suitably adapted parameterization of ventilation to represent heat transport with reasonable accuracy. To do so, only one site‐specific parameter, which is linked to the size of the pores in the blocky layer, is used. Inclusion of this ventilation parameterization is shown to be important for modeling the thermal regime at three experimental sites in the Swiss Alps. Furthermore, it could be shown that (i) snow depth dynamics exert a strong control on the thermal regime, (ii) the ice‐content stratigraphy needs to be known precisely and (iii) the augmented heat flux through the blocky layer caused by ventilation in both snow and blocks is important.